ANALISIS IMPLEMENTASI BALANCE SCORECARD SEBAGAI ALAT PENGUKURAN KINERJA PADA SMP KRISTEN PETRA KEDIRI (STUDI KASUS DI SMP KRISTEN PETRA KEDIRI) - Batu, Amat Pintu (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2017)
The purpose of this research is to know the Implementation of Balance Scorecard at SMP Kristen Petra Kediri, the performance of SMP Kristen Petra Kediri before Implementation of Balance Scorecard, the performance of SMP Kristen Petra Kediri after Balance Scorecard Implementation, to confirm whether the change of SMP Kristen Petra Kediri performance is caused by Balance Scorecard implementation or other causes. This research uses descriptive qualitative approach. This technique is chosen because with this technique the researchers can clearly illustrate the phenomenon that occurred in the place of research, precisely the phenomenon of Balance Scorecard implementation in SMP Kristen Petra Kediri. While data collection techniques are in-depth interviews and observations which then use triangulation. Data analysis techniques are done by reducing the data obtained, presenting and drawing conclusions. Keywords: Balance Scorecard, Perspective, Balance